Comparison of Modified Radical Mastectomy with Breast Conservative Surgery in term of Recurrence of Breast Cancer - Muhammad Khalid Iqbal, Muhammad Hussnain Iqbal, Syed Ahmer Gillani (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To compare the modified radical mastectomy with breast conservative surgery in term of recurrence of breast cancer. Material and methods: Between April 2021 to October 2021, total 60 women having age 30 years to 60 years were selected from Department of Surgery, D.G Khan Hospital, D.G Kahn. Type of study was randomized controlled trial. Recurrence rate of breast cancer was compared between the both groups. Results: Mean age was 43.83 ± 9.633 years mean duration of breast cancer was 5.43 ± 1.890 years. Total 5 (16.67%) patients of MRM group found with recurrence while in conservative surgery group, it was found in 13 (43.33%) patients. Significantly (P = 0.047) higher proportion of recurrence was noted in conservative surgery group as compared to MRM group. Conclusion: Results of present study revealed that recurrence rate of breast cancer is significantly high after breast conservative surgery as compared to modified radical mastectomy. 3rd and 4th decade of life was common. Keywords: MRM, breast cancer, breast conservative surgery, recurrence